2009
DOI: 10.1007/s10529-009-0098-y
|View full text |Cite
|
Sign up to set email alerts
|

A seed coat-specific promoter for canola

Abstract: The canola industry generates more than $11 billion of yearly income to the Canadian economy. One problem of meal quality is the dark polyphenolic pigments that accumulate in the seed coat. Seed coat-specific promoters are a pre-requisite to regulate the genes involved in seed coat development and metabolism. The beta-glucuronidase (GUS) reporter gene was used to test an Arabidopsis promoter in developing and mature seeds of canola (Brassica napus). The promoter tested is the regulatory region of the laccase g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
5
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 18 publications
3
5
0
Order By: Relevance
“…AtTT10 was mainly expressed in developing siliques and seeds, specifically in the seed coat [15], [16], [20], [30]. To verify the organ-specific function of Brassica TT10 genes, qRT-PCR was used to determine their mRNA levels in different organs of the black-seeded lines from the three Brassica species.…”
Section: Resultsmentioning
confidence: 99%
“…AtTT10 was mainly expressed in developing siliques and seeds, specifically in the seed coat [15], [16], [20], [30]. To verify the organ-specific function of Brassica TT10 genes, qRT-PCR was used to determine their mRNA levels in different organs of the black-seeded lines from the three Brassica species.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, Liang et al (2006) did not detect any activity in roots and leaves. Interestingly, the TT10 promoter construct studied by Liang et al (2006) was also shown to be active in the seed coat of canola (Brassica napus), but activity was restricted to outer integument (El-Mezawy et al, 2009).…”
Section: Flavonoid Polymerization In Seeds: Other Roles For Arabidmentioning
confidence: 99%
“…Testing the promoter activity of well-characterized Arabidopsis genes in Brassicaceae oilseed crop species is an attractive approach which bypasses the requirement of comprehensive transcriptome analysis in the target species to discover candidate promoters. Several Arabidopsis seed coat specific gene promoters including TT10, DP1, GILT [29], BAN [27], and ÎŽVPE [28] have been tested in canola [30,[33][34][35]. In this study, we tested the activity of Arabidopsis TT10 and DP1 promoters in two emerging biofuel oilseed crops, pennycress and camelina.…”
Section: Both Attt10 and Atdp1 Drive Gene Expression Predominantly In...mentioning
confidence: 99%
“…Several seed coatspecific genes have been experimentally identified in the model plant Arabidopsis thaliana [23,[27][28][29][30][31][32]. The promoter of some of these genes were shown to be able to drive gene expression in canola (Brassica napus) in a seed coat-specific manner [33][34][35]. Like canola, pennycress and camelina are members of the Brassicaceae family and are closely related to Arabidopsis [36].…”
Section: Introductionmentioning
confidence: 99%